Prospects for using CRISPR-Cas9 system in the treatment of human viral diseases - A. M. Ziganshin; A. R. Mulyukov; M. A. Omarov; V. A. Mudrov; R. Sh. Khalitova (Acta Biomedica Scientifica, 2023)
The aim. To analyze the possibility of using the genetic mechanisms of CRISPR-Cas9 technology in the prevention and treatment of certain viral diseases.Materials and methods. The search for publications was carried out in Russian and foreign literature using the following search engines: RSCI, Cyberleninka, eLibrary, PubMed, Cochrane Library, etc. A review of domestic and international scientific papers on the research topic was carried out using search keywords: CRISPR, genetic engineering, genome editing, Cas9, sgRNA.Results. A review of using CRISPR-Cas9 method (“genetic scissors”) as a gene therapy for some viral diseases was carried out, and its main advantages and disadvantages were revealed. An analysis of the data of scientific studies on genetic research methods over the past decade discovers the main aspects of CRISPR-Cas9 technology, modern classification and prospects for using this technology in clinical practice for the treatment and prevention of human viral diseases. The possibilities of creating a more versatile and stable version of the CRISPR-Cas9 technology are considered. Particular attention is paid to the technological difficulties and obstacles that scientists face when implementing this system for targeted use in clinical medicine.Conclusion. One of the rapidly developing areas in science giving promising prospects for modern healthcare is genetic engineering, especially in cases where scientific developments are applied in clinical practice. The discovery of “genetic scissors” technology has revolutionized all medicine. Wide opportunities for developing new treatment methods for many viral diseases and creating conditions for their early prevention opened up for the medical community. In the future, with the introduction of this technology into clinical practice, it will become possible to treat diseases that have not previously responded to ongoing therapy and were considered incurable.